2015
DOI: 10.1016/j.neuroimage.2015.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical evaluation of a promising C-11 labeled PET tracer for imaging phosphodiesterase 10A in the brain of living subject

Abstract: Phosphodiesterase 10A (PDE10A) plays a key role in the regulation of brain striatal signaling. A PET tracer for PDE10A may serve as a tool to evaluate PDE10A expression in vivo in central nervous system disorders with striatal pathology. Here, we further characterized the binding properties of a previously reported radioligand we developed for PDE10A, [11C]TZ1964B, in rodents and nonhuman primates (NHPs). The tritiated counterpart [3H]TZ1964B was used for in vitro binding characterizations in rat striatum homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…; Liu et al. ). According to the LoganREF model, the distribution volume ratio (DVR) of each ROI was calculated using a MATLAB (Mathworks Inc., Natick, MA).…”
Section: Methodsmentioning
confidence: 98%
See 4 more Smart Citations
“…; Liu et al. ). According to the LoganREF model, the distribution volume ratio (DVR) of each ROI was calculated using a MATLAB (Mathworks Inc., Natick, MA).…”
Section: Methodsmentioning
confidence: 98%
“…Animals were prepared for microPET studies as previously reported (Liu et al. ). About 1.5–2.5% isoflurane inhalation anesthesia was maintained throughout the microPET imaging sessions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations